2007
DOI: 10.1111/j.1872-034x.2007.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular balance of oxidative stress and cytoprotective molecules in damaged interlobular bile ducts in autoimmune hepatitis and primary biliary cirrhosis: In situ detection of 8‐hydroxydeoxyguanosine and glutathione‐S‐transferase‐pi

Abstract: In AIH, oxidative stress and DNA damage may be involved in the pathogenesis of bile duct injury in a manner similar to that found in PBC. However, relatively preserved intracellular glutathione may play a key role in preventing progressive bile duct loss following bile duct injury in AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…ROS are involved in apoptosis in the biliary epithelium, and the antioxidant system may play a role in protecting against the progression of biliary destruction [40]. In PBC, apoptosis can be prevented by the presence of a relatively preserved intracellular glutathione concentration; this factor plays a key role in preventing progressive bile duct loss following bile duct autoimmune injury [41,42]. In asymptomatic PBC, we showed that alcohol consumption, even in only low amounts (between 20 and 30 g/day), was predictive of the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are involved in apoptosis in the biliary epithelium, and the antioxidant system may play a role in protecting against the progression of biliary destruction [40]. In PBC, apoptosis can be prevented by the presence of a relatively preserved intracellular glutathione concentration; this factor plays a key role in preventing progressive bile duct loss following bile duct autoimmune injury [41,42]. In asymptomatic PBC, we showed that alcohol consumption, even in only low amounts (between 20 and 30 g/day), was predictive of the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma GSH peroxidase activity was significantly higher in AIH patients with elevated ALT values compared with normal controls [86]. In AIH patients, oxidative stress and DNA damage are involved in the bile duct injury similar to primary biliary cirrhosis [87]. Moreover, homologs of NADPH oxidases (NOXs) are major sources of ROS and are expressed in human livers with stage 2-3 AIH [88].…”
Section: The Non-genetic Role Of Vitamin D In Autoimmune Hepatitismentioning
confidence: 99%
“…Oxidative stress has been shown to be independently associated with more advanced stages of some cholangiopathies as for example PBC [141]. Furthermore, expression of 8-hydroxydeoxyguanosine (8-OHdG), a marker of oxidative DNA damage, was preferentially detected in the nuclei of damaged interlobular bile ducts in this cholangiopathy [142,143]. In response to DNA damage, the gene encoding the cyclindependent kinase inhibitor WAF1 (aka p21) is induced by upregulated p53; WAF1 is a potent and reversible inhibitor of cell cycle progression at both the G1 and G2 checkpoints, and upregulated WAF1 induces irreversible G1 arrest and apoptosis.…”
Section: Intrinsic Pathwaymentioning
confidence: 95%